Protecting Half the Planet and Transforming Human Systems Are Complementary Goals - Crist, Eileen; Kopnina, Helen; Cafaro, Philip; Gray, Joe; Ripple, William J.; Safina, Carl; Davis, John; DellaSala, Dominick A.; Noss, Reed F.; Washington, Haydn; Rolston, Holmes; Taylor, Bron; et al. (Frontiers in Conservation Science, 2021)
The unfolding crises of mass extinction and climate change call for urgent action in response. To limit biodiversity losses and avert the worst effects of climate disruption, we must greatly expand nature protection while simultaneously downsizing and transforming human systems. The conservation initiative Nature Needs Half (or Half Earth), calling for the conservation of half the Earth’s land and seas, is commensurate with the enormous challenges we face. Critics have objected to this initiative as harboring hardship for people near protected areas and for failing to confront the growth economy as the main engine of global ecological destruction. In response to the first criticism, we affirm that conservation policies must be designed and implemented in collaboration with Indigenous and local communities. In response to the second criticism, we argue that protecting half the Earth needs to be complemented by downscaling and reforming economic life, humanely and gradually reducing the global population, and changing food production and consumption. By protecting nature generously, and simultaneously contracting and transforming the human enterprise, we can create the conditions for achieving justice and well-being for both people and other species. If we fail to do so, we instead accept a chaotic and impoverished world that will be dangerous for us all.